The Influence of Firm-Specific, Industry-Specific, Macroeconomic Factors, and Risk-Based Capital (RBC) on the Profitability of Life Insurance Companies in Indonesia - Ardila Galuh Savitri (Eduvest - Journal of Universal Studies, 2025)
This study aims to determine the influence of Firm-specific, Industry-specific, Macroeconomic factors, and Risk Based Capital (RBC) on the profitability of life insurance companies in Indonesia. This study uses secondary data, namely financial statement data of life insurance companies in Indonesia, macroeconomic data, and other information available on company websites, AAJI, OJK, and other sources. The data period used covers 2019 to 2023. The analysis method applied is regression analysis. Findings show that previous research conducted by Killins (2020) in Canada found that firm-specific factors such as liquidity and economic growth influence company profitability, while company size has a negative relationship with profitability. Industry-specific factors did not yield significant results related to profitability. Macroeconomic factors such as GDP growth and equity return show a significant influence on company profitability. In a study conducted by de Haan and Kakes (2010) in the Netherlands, it was shown that insurance companies with high profitability tend to have better solvency levels. The findings of this study can provide insights for life insurance companies in Indonesia regarding the factors that influence their profitability. This study contributes to understanding how Firm-specific, Industry-specific, Macroeconomic factors, and Risk Based Capital (RBC) affect the profitability of life insurance companies in Indonesia.